2017
DOI: 10.21608/ajfm.2017.18309
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Acute Organophosphate Poisoning Using Glasgow Coma Sale, Serum Cholinesterase and S100B

Abstract: All rights reserved. Introduction rganophosphates are the most widely used pesticides for killing agricultural pests all over the world as a result of its availability, low coast, and rapid degradation. Despite all efforts to improve management of them, accidental and suicidal ingestion is still a major public health problem. They are life-threatening condition associated with high morbidity and mortality especially in developing countries (Coskun et al., 2015). Organophosphates compounds deposit a phosphoryl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Pseudocholinesterase was reduced in the moderate and severe group pseudocholinesterase level. These data suggested that S100B may be a useful marker in the assessment of clinical severity and prediction of mortality in acute OP (Oreby and El madah 2017). The Aβ protein is an acute phase protein; its elevation in serum is one of the most rapid and intense sensitive markers in neurodegenerative disease (Jenna et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudocholinesterase was reduced in the moderate and severe group pseudocholinesterase level. These data suggested that S100B may be a useful marker in the assessment of clinical severity and prediction of mortality in acute OP (Oreby and El madah 2017). The Aβ protein is an acute phase protein; its elevation in serum is one of the most rapid and intense sensitive markers in neurodegenerative disease (Jenna et al 2019).…”
Section: Discussionmentioning
confidence: 99%